The origins of ISIS : the collapse of nations and revolution in the Middle East - Mabon, Simon; Royle, Stephen (Writer on the Middle East) (London ; New York : I.B. Tauris, 2017)
The rapid expansion of ISIS and its swathe of territorial gains across the Middle East have been headline news since 2013. Yet much media attention and analysis has been focussed upon the military exploits, brutal tactics and radicalisation methods employed by the group. While ISIS remains a relatively new phenomenon, it is important to consider the historical and local dynamics that have shaped the emergence of the group in the past decade. In this book Simon Mabon and Stephen Royle provide the reader with a comprehensive overview of the roots, tactics and ideology of the group, exploring the interactions of the various participants involved in the formative stages of ISIS. Based on original scholarly sources and first-hand research in the region, this book provides an authoritative and closely-analysed look at the emergence of one of the defining forces of the early twenty-first century.
Sovereignty, political organisation and the rise of ISIS -- Political organisation and the state in Iraq -- The sectarian house of cards -- Tribalism and the state -- The roots of Sunni militancy and its enduring threat in Iraq -- The human tragedy.
Includes bibliographical references (pages 199-219) and index.
Keywords: IS (Organization); Terrorism -- Middle East; Religious fundamentalism -- Middle East; HISTORY / Modern / 21st Century; SOCIAL SCIENCE / Islamic Studies; Religious fundamentalism; Terrorism